Durvalumab in frail and elderly patients with stage four non-small cell lung cancer: study protocol of the randomized phase II DURATION trial - Kuon, Jonas; Hommertgen, Adriane; Krisam, Johannes; Lasitschka, Felix; Stenzinger, Albrecht; Blasi, Miriam; Bozorgmehr, Farastuk; Maenz, Martin; Kieser, Meinhard; Schneider, Marc; Thomas, Michael (Trials, 2020)
Elderly patients represent a major fraction of non-small cell lung cancer (NSCLC) patients in routine clinical practice, but they are still underrepresented in clinical trials. In particular, data regarding efficacy and safety in frail or elderly patients with respect to immunotherapy are lacking. Importantly, immunosenescence in elderly patients might interfere with activities of immune-modulating drugs such as PD-1/PD-L1 inhibitors. Thus, there is an urgent need to assess safety and efficacy of such inhibitors in this group.
Gesehen am 03.06.2020